2008
DOI: 10.1017/s0022112008003650
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of swirl accumulation in a magnetically driven flow

Abstract: Independent poloidal and azimuthal body forces are induced in a liquid metal cylinder by travelling and rotating magnetic fields of different frequencies, respectively. The bulk axial and azimuthal velocities are measured by the ultrasound Doppler method. Particle image velocimetry is used to observe the upper free surface velocity distribution. The transition from the poloidal to the azimuthal body force governed regime occurs at a fixed ratio of the respective force magnitude of around 100. This transition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…At sufficiently high Ta numbers, the eyes of such vortex structures are situated close to the cylinder walls, whereas the poloidal flow in the core of the cylinder is found to be very weak. [21,26] The arrangement of the vortices is axisymmetric and mirror symmetric with respect to the horizontal midplane in an enclosed cylinder. Otherwise, the meridional recirculation is dominated by the lower vortex if a free surface exists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At sufficiently high Ta numbers, the eyes of such vortex structures are situated close to the cylinder walls, whereas the poloidal flow in the core of the cylinder is found to be very weak. [21,26] The arrangement of the vortices is axisymmetric and mirror symmetric with respect to the horizontal midplane in an enclosed cylinder. Otherwise, the meridional recirculation is dominated by the lower vortex if a free surface exists.…”
Section: Resultsmentioning
confidence: 99%
“…Each transducer acquired directly the velocity component projected on the ultrasound beam line. The distribution of the fluid azimuthal velocity along the cylinder radius can be reconstructed based on the method described by Grants et al [26] In the experiment, we determined also the vertical velocity profiles by arranging an array of transducers vertically along the diameter at the cylinder bottom. Figure 1(a) shows an example with a single transducer at the center of the cylinder bottom.…”
Section: Methodsmentioning
confidence: 99%
“…This swirl accumulation can even produce tornado-like flow structures in a laboratory scale. 28,29) The effect of swirl accumulation becomes visible by strong deformations of the free surface. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a combination of these two types of magnetic fields may be suitable for a wide range of shapes. A helical magnetic field can be obtained in this way using current-carrying coils [5][6][7][8][9] or a permanent magnetic field. [10][11][12] Vive`s et al [10][11][12] designed a helical permanent magnetic field to stir a semi-solid melt and mix the secondary phase (i.e., the micro-scale particles within the semi-solid melt) to fabricate metal matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…The meridional flow patterns can exhibit either meridian secondary flow (two vortices) or global axial flow (one vortex) depending on the operating parameters. [5,8,13] Grants et al [8] reported a transition between these two flow patterns based on the current-carrying coil type of the helical magnetic field. In this case, the meridian secondary flow pattern can remain unchanged when the rotating direction of a helical magnetic field is alternated.…”
Section: Introductionmentioning
confidence: 99%